"When did you see her last?" - Snicket, Lemony; Art by Seth (London Egmont Publishers, 2013)
In the fading town of Stain'd-by-the-Sea, young apprentice Lemony Snicket has a new case to solve when he and his chaperone are hired to find a missing girl. Is the girl a runaway? Or was she kidnapped? Was she seen last at the grocery store? Or could she have stopped at the diner? Is it really any of your business?
Keywords: Missing persons--Investigation -- Missing children -- Secret societies